Sustentabilidade dos municípios do COREDE Alto Jacuí : avaliação e diretrizes de melhoria - Locatelli, Mirian Daiana (2011)
The theme of this research is the sustainable development of the region of Rio Grande do Sul, Alto Jacuí COREDES . The objective is to analyze the sustainability of municipalities of the Regional Development Council of Alto Jacuí (COREDES) through the Index of Sustainable Development for Cities (ISDC), thus aiming to generate contributions that help the sustainability of each local municipality. Fourteen cities of Alto Jacuí COREDES were analyzed in six of the tool dimensions: social, demographic, economic, political, institutional, environmental and cultural. A database from information gathered from reliable sources was compiled which were transformed into indices for analysis. After examining the indices, the strengths and weaknesses of each municipality were checked. From these results, recommendations and guidelines have been developed that may contribute to public policy decision making in the areas that need more investment to improve the sustainability of municipalities of Alto Jacuí COREDES. The ISDC was calculated from the average of the Social, demographic, economic, political, institutional, environmental and cultural indices. The ISDC of the cities of Alto Jacuí COREDES provides information of significant relevance to the definition of public policies, to establish the foundation for the sustainable development process. The ISDC of municipalities of Alto Jacuí COREDES showed the following: no city has the optimal level of sustainability and 28.57% have acceptable level, 71.43% alert leveland no city has a critical level